2008
DOI: 10.2355/isijinternational.48.584
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Effects of Electromagnetic Brake and Argon Gas Injection on the Three-dimensional Multiphase Flow and Heat Transfer in Slab Continuous Casting Mold

Abstract: A 3-D mathematical model has been developed to study the multiphase phenomena of magnetic field, flow field and temperature distribution of molten steel and inclusion behaviour, considering the coupled effects of electromagnetic brake (EMBR) and argon gas injection in the slab continuous casting mold with high casting speed. The effects of EMBR and argon gas injection on the flow and temperature of molten steel and inclusion removal rate have been investigated. Simulation results indicate that EMBR can slow do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…8(b). Higher surface velocities are found towards the quarter point, midway between the SEN and the NF, as typical for a doubleroll flow pattern 13,17,35) The highest velocity is found closer to the OR. Surface velocity fluctuations are consistently very large ~0.12 m/sec across the entire mold width.…”
Section: Surface Velocitymentioning
confidence: 81%
See 1 more Smart Citation
“…8(b). Higher surface velocities are found towards the quarter point, midway between the SEN and the NF, as typical for a doubleroll flow pattern 13,17,35) The highest velocity is found closer to the OR. Surface velocity fluctuations are consistently very large ~0.12 m/sec across the entire mold width.…”
Section: Surface Velocitymentioning
confidence: 81%
“…[11][12][13][14][15][16][17][18][19][20][21] However, there is less study on the effect of gas on transient flow. [22][23][24][25][26] Using a standard steady-state k-ε model, Bai and Thomas found that increasing argon gas volume fraction or bubble diameter bends the jet angle more upward and also increases turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…These concerns have been investigated in many CFD studies focusing on SEN port designs, SEN submerged depths, argon injection, electromagnetic braking, and so on. [18][19][20][21][22][23][24][25] Among them, the particle-capture model developed by Thomas et al [25] gives a good contribution to describe the particle capture behavior at the solidifying front, since it represents a good physical framework by considering the local force balances.…”
Section: Introductionmentioning
confidence: 99%
“…Trajectories, distribution and removal of inclusion in mold with electromagnetic brake (EMBr) or argon gas injection were simulated in Refs. [12][13][14]. A lot of work (Refs.…”
Section: Introductionmentioning
confidence: 99%